Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

If n th term is n²+1 then, the difference between nth term and n+1 th term is:

(n+1)² + 1 - n² - 1 = 2n +1

So the common difference changes with n. and is not a constant. Hence, the nth term cannot be n²+1 in an AP.

========================

Let the arithmetic series be:

a , a + d, a + 2 d, a + 3 d, ..... a + (n - 1) d

Let assume that the nth term is equal to n²+1,

So a + (n - 1) d = n² + 1

n² - n d + (1+d -a) = 0

n is an integer if d² - 4 d + 4a -4 is real, a perfect square and then its square root added to +d or -d is an even integer.

d² - 4 d + 4 (a-1) is real and perfect square only if the discriminant is 0.

4² - 16 (a - 1) = 0

=> a = 2

Now, d + (d-2) = 2 (d - 1) must be an even integer. Which is true if d is an integer.

OR, d - (d - 2) must be an even integer, which is true,

now n = d - 1 or 1

case 1) n = d - 1 => d = n+1 and a = 2

2, 2+n+1, 2+2(n+1), 2 + 3 (n+1) , ....

2, 5, 10, 17, ...__This is not an Arithmetic Progression. __

case 2) 2, 2+d, 2+2 d, 2+3d , 2+4 d

It seems only one term or two terms can satisfy the condition that n the term is n² + 1. Like in

2, 5, 8, 11 .... : only the first two terms satisfy the condition.

or 2, 6, 10, 14, ... : the first and 3 rd terms satisfy the condition.

So it is clear and proved that the nth term of an AP cannot be n²+1.

(n+1)² + 1 - n² - 1 = 2n +1

So the common difference changes with n. and is not a constant. Hence, the nth term cannot be n²+1 in an AP.

========================

Let the arithmetic series be:

a , a + d, a + 2 d, a + 3 d, ..... a + (n - 1) d

Let assume that the nth term is equal to n²+1,

So a + (n - 1) d = n² + 1

n² - n d + (1+d -a) = 0

n is an integer if d² - 4 d + 4a -4 is real, a perfect square and then its square root added to +d or -d is an even integer.

d² - 4 d + 4 (a-1) is real and perfect square only if the discriminant is 0.

4² - 16 (a - 1) = 0

=> a = 2

Now, d + (d-2) = 2 (d - 1) must be an even integer. Which is true if d is an integer.

OR, d - (d - 2) must be an even integer, which is true,

now n = d - 1 or 1

case 1) n = d - 1 => d = n+1 and a = 2

2, 2+n+1, 2+2(n+1), 2 + 3 (n+1) , ....

2, 5, 10, 17, ...

case 2) 2, 2+d, 2+2 d, 2+3d , 2+4 d

It seems only one term or two terms can satisfy the condition that n the term is n² + 1. Like in

2, 5, 8, 11 .... : only the first two terms satisfy the condition.

or 2, 6, 10, 14, ... : the first and 3 rd terms satisfy the condition.

So it is clear and proved that the nth term of an AP cannot be n²+1.

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

This is your answer.